Arginine related amino acids in hypertension in a local South African cohort - Naidoo, Cameron Aston (My University, 2012)
Background: Hypertension is an important modifiable risk factor for cardiovascular disease, the leading cause of mortality and morbidity globally. Blood pressure can be reduced by vasodilators, such as drugs and the semi-essential amino acid arginine, the precursor of the potent vasodilator nitric oxide. Although arginine supplementation has been used to reduce blood pressure, plasma arginine concentrations have been shown to be increased in hypertension. This study measured the concentrations of urinary and plasma amino acids and described associations between arginine related amino acids and their associations with 24 hour ambulatory blood pressure concentrations in Black South African control subjects and patients with hypertension. Methods: Ninety-seven participants were recruited at the clinics, hospitals and laboratories in Johannesburg area. Twenty four hour ambulatory blood pressure readings were obtained and early morning fasting blood and urine sample were taken with a medical history. Amino acids concentrations were determined using high performance liquid chromatography and mass spectrometry. Results: Plasma and urinary amino acid concentrations were unchanged in patients with elevated blood pressure compared with normotension. Arginine concentrations correlated positively with amino acids using the same transporter, other urea cycle amino acids, the inhibitor asymmetric dimethylarginine , and strongly with its precursor proline (r2>0.9; p<0.0001) even after correcting for amino acid nitrogen (r2>0.7; p<0.0001). Elevated urinary arginine concentrations were found to be an independent determinant of both daytime systolic and diastolic blood pressures, with citrulline excretion determining both 24 hour and daytime diastolic pressures. Lysine also correlated with blood pressure and was found to be an independent predictor of blood pressure in multivariate analysis
M.Sc. (Med.), Faculty of health Sciences, University of the Witwatersrand, 2011
Keywords: Hypertension